2017
DOI: 10.1002/ags3.12005
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of circulating tumor cells in blood from patients with gastric cancer

Abstract: Circulating tumor cells (CTC) have been focused on as a target for detecting occult tumors, predicting therapeutic responses and prognoses, and monitoring postoperative recurrence in the clinical management of patients with various malignancies, including gastric cancer. Recent advances in molecular diagnostic tools have contributed to high sensitivity and specificity for the detection of CTC. A conspicuous disparity exists in the incidence of CTC among studies. However, a close relationship has been reported … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…Although CK + EpCAM + CTCs were detectable in peripheral blood, CK + EpCAM + CTC was not associated with poor prognosis in this study. It has been reported that CK‐positive or EpCAM‐positive CTCs were not correlated with the prognosis of patients with a solid tumor including GC 34,35 . These findings suggest that CK + EpCAM + CTCs might not have high malignant potential for GC patients.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Although CK + EpCAM + CTCs were detectable in peripheral blood, CK + EpCAM + CTC was not associated with poor prognosis in this study. It has been reported that CK‐positive or EpCAM‐positive CTCs were not correlated with the prognosis of patients with a solid tumor including GC 34,35 . These findings suggest that CK + EpCAM + CTCs might not have high malignant potential for GC patients.…”
Section: Discussionmentioning
confidence: 82%
“…12,13 One of the reasons for the negative results of clinical studies of CTCs were not correlated with the prognosis of patients with a solid tumor including GC. 34,35 These findings suggest that CK + EpCAM + CTCs might not have high malignant potential for GC patients. On the other hand, our results indicated that the prognosis of patients with FGFR2 + CTCs was significantly poorer than that of patients without FGFR2 + CTCs.…”
Section: Discussionmentioning
confidence: 87%
“…For instance, circulating tumor cells (CTC) have been discussed as a clinical tool to detect early stages, disease recurrence, and tumor progression in gastric cancer. Arigami et al reviewed the current data to CTC for gastric cancer, concluding that there have been contradictory studies so far [112]. However, by making use of new technologies for the isolation and enrichment of tumor cells, it may be possible to improve CTC detection using novel promising markers.…”
Section: Prospective Diagnostic and Therapeutic Strategiesmentioning
confidence: 99%
“…However, the clinical significance of PD‐L1 expression in blood specimens of patients with gastric cancer has not yet been assessed. Naturally, non‐invasive liquid biopsy using blood specimens has the clinical attractiveness of being a simple and repeatable sampling tool …”
Section: Introductionmentioning
confidence: 99%
“…Naturally, non-invasive liquid biopsy using blood specimens has the clinical attractiveness of being a simple and repeatable sampling tool. 13 The aim of this study was to investigate PD-L1 expression in blood specimens and to assess the relationships between PD-L1 expression and clinicopathological features, including prognosis, in patients with gastric cancer.…”
Section: Introductionmentioning
confidence: 99%